STUDENTS' EXPERIENCES IN USING DIGITAL ANNOTATION TOOLS TO ENHANCE READING COMPREHENSION - Feri Ferdiyanto; Muhammad Nawawi Ivan; Zanubah Arifah Khofsoh (J-Shelves of Indragiri (JSI), 2026)
The rapid proliferation of digital technologies in educational settings has fundamentally transformed how students engage with academic texts. Among the many tools that have emerged, digital annotation tools - software applications that enable readers to highlight, comment, tag, and organize information within digital documents - have attracted considerable scholarly interest. Despite growing enthusiasm in both practitioner communities and research circles, relatively little attention has been paid to how students themselves experience the use of these tools, particularly in relation to reading comprehension development. This qualitative study explores the lived experiences of 24 undergraduate EFL (English as a Foreign Language) students enrolled at a state university in Indonesia who used digital annotation tools - specifically Hypothesis, Kami, and Adobe Acrobat Reader - over one full academic semester. Drawing on semi-structured interviews, reflective journals, and classroom observations, the study examines students' perceptions of tool usability, their emerging annotation strategies, and the ways in which tool use influenced their reading comprehension processes and outcomes. Findings reveal that digital annotation tools fostered deeper textual engagement by encouraging active reading behaviors, facilitating meaning negotiation, and promoting metacognitive awareness. Students reported marked improvements in their ability to identify main ideas, make inferences, and critically evaluate source texts. However, challenges related to digital literacy, screen fatigue, and technological access also surfaced as notable barriers. The study contributes nuanced, student-centered insights into the pedagogical affordances and limitations of digital annotation tools and offers practical recommendations for educators seeking to integrate these tools meaningfully into reading instruction.